Let $X$ be a random variable which follows an exponential distribution with parameter $\lambda (\lambda > 1)$. Define a new random variable $Y$ by $$Y = e^X$$ Find the CDF of $Y$.

So is this saying that I need to find the CDF of $\lambda e^{-\lambda x}$ or $e^{\lambda e^{-\lambda x}}$?

Edit: This is the answer I came up with although not entirely sure if this is correct.

$$F_y(y) = P(e^X \leq y) = P(X \leq ln(y)) = F_x(ln(y))$$ $$ F_y(y) = \begin{cases} 1-e^{-\lambda ln(y)} & y \geq 0 \\ 0, & otherwise \end{cases} $$ $$f_y(y) = \frac{1}{y} f_x(ln(y))$$

$$E[Y] = \int_{1}^{\infty} f_x(ln(y)) dy$$

Feel free to correct me if I'm wrong.

  • $\begingroup$ you will find the CDF of the random variable $Y=e^X$, where $X$ is exponentially distributed. So your question in the last line makes no sense. $\endgroup$ May 23, 2017 at 23:31
  • $\begingroup$ The constant confusion between $X$ and $Y$ vs $x$ and $y$, does not help your understanding. A first step would be to reach some amount of rigor in this respect. $\endgroup$
    – Did
    May 27, 2017 at 9:28
  • $\begingroup$ Please enlighten me then. $\endgroup$
    – saechaoc
    May 27, 2017 at 17:41

2 Answers 2


Neither $\lambda e^{-\lambda x}$ nor $e^{\lambda e^{-\lambda x}}$ is $Y$.

$Y$ is $e^X$, so find the CDF of $Y$ means compute $P(Y\leq y) = P(e^X\leq y)$.

  • $\begingroup$ Ok thank you! The confusion I had was since X is exponentially distributed I assumed it was $\lambda e ^{-\lambda x}$ but that makes more sense. $\endgroup$
    – saechaoc
    May 24, 2017 at 0:09


$$f(x) = \lambda e^{-\lambda x}$$

with domain of support given by $\{x,\ 0,\ \infty \}$.

The transformed random variable,

$$Y = \exp(X)$$

gives the new distribution

$$f(y) = \frac{1}{y^{1+\lambda}}$$

with domain of support $\{y,\ 1,\ \infty \}$

  • $\begingroup$ I calculated it the following way, we have $F_Y(y) = P(X \leq \ln(y))$, from $F_X(x) = P(X \leq x) = 1-e^{-\lambda x}$, for $x \geq 0$, we have then $F_Y(y) = P(X \leq \ln(y)) = 1 - e^{-\lambda \ln(y)} = 1 - y^{-\lambda}$. Then $f_Y(y) = \frac{d}{dy}F_Y(y) = (1 - y^{-\lambda})' = \lambda y^{-\lambda - 1}$. But your $f(y) = \frac{1}{y^{1+y}}$, so my question is, what did I wrong? $\endgroup$
    – P_Gate
    Mar 25, 2021 at 16:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.